Navigating challenges in management of drug resistant tuberculosis: Case experience from Nepal - Verma, Avatar; Bhatta, Narendra; Mishra, Deebya Raj; Acharya, Achyut Bhakta; Shahi, Rejina; Limbu, Sion Hangma; Katuwal, Srijan (Nepalese Respiratory Journal, 2022)
Drug resistant tuberculosis (DR TB) a severe form of TB is a disease of concern. Its treatment requires multiple toxic drugs for prolonged duration because of which, often have complicated course requiring close supervision, continuous encouragement from physician, management of side effects and modification of drug regimen for successful outcome. In this report, we are presenting a case of diabetic patient suffering from DR TB highlighting key diagnostic and management challenges.